A northern planner's perspective: One opinion - Robertson, Ian D. (Canadian Institute of Planners, 1999)
Determining whether land-use planning in Canada's north has been successful is a question of perspective, attitude and political expectation. Most planning activity over the past thirty years has been reactionary rather than anticipatory - the result of external pressures over which people living here have little control. A "top-down" regional planning process directed by the Department of Indian Affairs and Northern Development failed because of inequalities in power, a lack of measurable objectives, and the absence of a shared vision. The settlement of land claims and the division of the Northwest Territories has created new opportunities for a community-driven, ecosystem-based approach to land and resource management. However, because no one asked the fundamental question of how much government is actually needed by 60,000 people, these changes have also increased the amount of bureaucracy. Most planners come north by choice, bringing along their southern background, training and perspective. The government towns of Goose Bay, Yellowknife and Whitehorse generally exhibit the developed form, attitudes to planning, and policy development found down south. In terms of physical layout and built form, traditional solutions area replicated from coast to coast. Planners have generally avoided the more complex social and economic problems. Planners need interdisciplinary, cross-cultural and community-development skills. They must understand how the contextual issues of scale, regional geography, and time affect their work, and be prepared to make the personal commitment required to become part of the communities in which they work. Prétendre que l'aménagement du territoire dans le Nord canadien est un succès ou un échec est une question de point de vue et de choix politique. La démarche des urbanistes au cours des trente dernières années était plus souvent faite d'opportunisme que d'anticipation; c'est-à-dire qu'elle a été et plus souvent l'objet de pressions extérieures hors de contrôle des populations locales. L'échec du projet d'urbanisme régional dirigé par le ministère des Affaires indiennes det du Nord canadien est dû à des inégalités dans l'attribution des pouvoirs et à un manque d'objectifs mesurables et de visions communes. Depuis le règlement des revendications territoriales et la division des Territoires du Nord-ouest on peut entrevoir une gestions des terres et des ressources dirigée par la communauté et basée sur l'écosystème. Toutefois, ces changements on engendré davantage de bureaucratie car la question de la proportion des ressources gouvernementales pour une population de 60000 personnes n'a jamais été posée. L plupart des urbanistes qui s'installent dans le nord, le font par choix personnel et apportent du sud leur expérience, leur compétence et leurs visions. Les villes de Goose Bay, Yellowknife our Whitehorse rappellent généralement les modèles de développement, d'urbanisme et d'élaboration des politiques du sud du Canada. Les solutions traditionnelles se répètent d'un océan à l'autre. Les urbanistes ont la plupart du temps évité d'aborder les problèmes, plus complexes, du tissu social et économique. Les urbanistes doivent acquérir une formation plurisciplinarie, intercultureele et des connaissances sur le développement communautaire. Ils doivent tenir compte des problèmes d'échelle, de temps et de géographie particuliers à la région et se préparer à investir les efforts nécessaires pour s'intégrer à la communauté pour laquelle ils travaillent. Abstract in English and French; text in English. https://viurrspace.ca/bitstream/handle/10613/6506/Robertson.pdf?sequence=3